ALLOCATION OF PROFIT TO MEMBERS OF LIMITED LIABILITY COMPANY AND DIFFERENCES IN RELATION TO OTHER CORPORATE LEGAL PAYMENTS - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Given that there is a relatively large number of professional and scientific papers in the domestic scientific literature dealing with the economic issue of dividend payment policy, and that few are devoted to the legal aspects of profit sharing, the subject of this paper will be discussed analysis of the regulation relating to the distribution of profits to members of a limited liability company. Also, since in business practice there is often no correct understanding of the legal nature of the various payments to members of a limited liability company who also originate from the same initial bookkeeping source of funds - balance sheet profit, the work will also make a clear distinction between the payment of profits in relation to other payments of a corporate-legal nature.